2020
DOI: 10.1126/sciadv.aaz1002
|View full text |Cite
|
Sign up to set email alerts
|

Recursive sequence generation in monkeys, children, U.S. adults, and native Amazonians

Abstract: The question of what computational capacities, if any, differ between humans and nonhuman animals has been at the core of foundational debates in cognitive psychology, anthropology, linguistics, and animal behavior. The capacity to form nested hierarchical representations is hypothesized to be essential to uniquely human thought, but its origins in evolution, development, and culture are controversial. We used a nonlinguistic sequence generation task to test whether subjects generalize sequential groupings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 45 publications
0
79
0
Order By: Relevance
“…Implicit mentalizing abilities have been described in chimpanzees and macaques 77 , 78 , and are affected by reversible lesions of the ACC in macaques 78 . Recursive thinking and counterfactual manipulation of information to guide behavior have also been observed in macaques 75 , 79 . Counterfactual reasoning was also impacted by reversible lesions of the ACC in macaques 75 .…”
Section: Discussionmentioning
confidence: 93%
“…Implicit mentalizing abilities have been described in chimpanzees and macaques 77 , 78 , and are affected by reversible lesions of the ACC in macaques 78 . Recursive thinking and counterfactual manipulation of information to guide behavior have also been observed in macaques 75 , 79 . Counterfactual reasoning was also impacted by reversible lesions of the ACC in macaques 75 .…”
Section: Discussionmentioning
confidence: 93%
“…A great variety of non-exclusive hypotheses have been proposed to account for human singularity, including the emergence of evolved mechanisms for social competence (1), pedagogy (2), natural language (3,4), or recursive structures across multiple domains such as language, music and mathematics (5)(6)(7)(8). Unfortunately, few experimental paradigms, mostly in the domain of artificial grammar learning, afford a direct comparison of human and non-human primate behavior using the same methods (9)(10)(11)(12)(13)(14). Here, we present experimental investigations of the differences between humans and baboons in the domain of geometry, and more specifically, the visual perception of quadrilaterals such a square, a rectangle or a parallelogram.…”
Section: Main Textmentioning
confidence: 99%
“…A prominent hypothesis is that the capacity to represent embedded structures may be specific to the human species (Fitch, 2014;Hauser et al, 2002). Indeed, several comparative studies found that, while human and non-human primates exhibit similar performance in sequence processing whenever sequential relations, statistical properties or simple nonadjacent dependencies suffice to perform the task (Hauser et al, 2001;Milne et al, 2016Milne et al, , 2018Newport et al, 2004;Ravignani et al, 2013;Sonnweber et al, 2015;Wilson et al, 2013Wilson et al, , 2017, important differences are observed when the sequences involve embedding or recursion (Ferrigno et al, 2020;Fitch, 2004;Jiang et al, 2018;Wang et al, 2015). For instance, in a spatial motor task, although macaque monkeys could learn a supra-regular grammar and generalize it to novel sequences, they need a training period of thousands of trials to achieve the performance level that preschool children reach in only a few trials (Jiang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although the acquisition of simple embedded sequences may not be out of reach of macaque monkeys (Ferrigno et al, 2020;Jiang et al, 2018), the difference between human and non-human primates may originate, at least in part, in human's ability to rapidly acquire complex sequential rules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation